Analysis of commuter movements on main access routes to the city of Lisbon using cell phone data - Sousa, Ricardo Nuno Costa Moinhos Santos de (2024)
This work aims to tackle the problem of congestion on the main access roads to the city of Lisbon, and the main factors behind it. With the help of the Lisbon City Council, via Lx Data Lab, which provided the date obtained from a contract already established with a mobile operator and with IPMA, where it is possible to generate events completely anonymously through the signalling exchanged between the mobile network and the user's terminal to obtain information on the volume of entries and exits every 5 minutes at the 11 access points to the city during the period from September 2021 to December 2022. They also provided access to the weather and rainfall conditions during the same period of analysis, allowing a comparison to be made between these conditions and the volume of inflows and outflows, characterising them during the morning and afternoon rush hour periods and with variables such as school and holiday periods. This work aimed to: 1) create knowledge about the problems of congestion and traffic management; 2) identify the possible factors and time periods with the most traffic; 3) visualise and analyse the work carried out in order to extract knowledge that will help decision-making in tackling the problem of congestion. An LTSM model was used to make short-term forecasts, which obtained good results both in terms of its ability to predict the patterns of rise and fall of the real values and in obtaining a low loss value in the validation set.